Development of fungal spore staining methods for flow cytometric quantification and their application in chlorine-based disinfection. (March 2020) - Wen, Gang; Cao, Ruihua; Wan, Qiqi; Tan, Lili; Xu, Xiangqian; Wang, Jingyi; Huang, Tinglin
Abstract: Fungal contamination in drinking water has been becoming a hot topic. The routine enumeration method of fungal spores is heterotrophic plate counts (HPC). However, this method is time-consuming and labor-intensive and there is also the difficulty of enumerating viable but non-culturable cells. In this study, a rapid, simple and accurate method for quantifying fungal spores and discriminating their viability in water was established using flow cytometry (FCM) combined with fluorescence dyes. The optimal staining conditions are as follows: spores suspensions are sonicated at 495 W for 5 min as pretreatment, and then 10 μL of SYBR Green I (100×) and 30 mM Ethylene diamine tetraacetic acid are added to a 500 μL water sample, which incubate at 35 °C for 20 min in dark. The concentration of fungal spores measured by FCM was highly correlated with HPC results and microscope observations, with correlation coefficient of 0.996 and 0.988, respectively. This staining method can be widely applied to the enumeration and viability evaluation of fungal spores. In addition, chlorine-based inactivation of three genera of fungal spores was assessed by plating and FCM. The result showed that all three genera of fungal spores lost culturability firstly and then membrane integrity decreased, preliminarily revealing the inactivation mechanism. The inactivation rate constants of membrane damage varied in the following order: chlorine dioxide > chlorine > chloramine. This study concluded that FCM is an appropriate and alternative tool to detect fungal spores' viability and can be used for evaluating the fungal inactivation by disinfectants. Graphical abstract: Image 1 Highlights: The enumeration and viability assessment of fungal spores by FCM were developed. Fungal spores lost culturability firstly and then became membrane compromised during inactivation. The efficiency of causing membrane damage was in order: chlorine dioxide > chlorine > chloramine.